2020
DOI: 10.1016/j.dsx.2020.05.037
|View full text |Cite
|
Sign up to set email alerts
|

Does poor glucose control increase the severity and mortality in patients with diabetes and COVID-19?

Abstract: Background and aim: Diabetes in often associated with an increased severity and mortality in patients with COVID-19. We aimed to find out whether the severity and mortality in patients with diabetes with COVID-19 has any correlation to the level of glycemic control. Methods: A Boolean search was made in PubMed database using the specific keywords related to our objectives up till May 14, 2020 and full text of article retrieved with the supplements published in English language. Results: Two studies available s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
3
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 10 publications
4
52
3
2
Order By: Relevance
“…In regard to COVID-19, elevated blood glucose(BG) levelsis also associated with in-hospital complications, including mechanicalventilation requirement, intensive care unit (ICU) admission, and death [3][4][5][6][7].Thus, hyperglycemia, particularly upon admission, could be a marker of poor prognosisregardless of diabetes status. This suggests that elevated BG may play a decisiverole in the severityof the disease at an early stage [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In regard to COVID-19, elevated blood glucose(BG) levelsis also associated with in-hospital complications, including mechanicalventilation requirement, intensive care unit (ICU) admission, and death [3][4][5][6][7].Thus, hyperglycemia, particularly upon admission, could be a marker of poor prognosisregardless of diabetes status. This suggests that elevated BG may play a decisiverole in the severityof the disease at an early stage [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Santiago Clinical Hospital, Santiago de Compostela, Spain (8) Internal Medicine Department. Torrevieja University Hospital, Torrevieja, Spain (9) Internal Medicine Department. Nuestra Señora del Prado Hospital, Talavera de la Reina, Spain…”
mentioning
confidence: 99%
“…However, numerous studies have shown an increased risk of severe COVID- 19 and mortality in individuals with diabetes [4,[6][7][8][9][10][11][12], as well as higher rates of hospitalization due to COVID-19 [13,14]. Thus, individuals with diabetes have been identified as having worse COVID-19 outcomes, particularly those with poor glycemic control [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The mortality rate was significantly higher in patients with pre-existing DM compared to non-diabetic individuals (7.8% versus 2.7%, p <0.001; adjusted risk ratio of 1.49). 25 Furthermore, after a 28-day follow-up, 528patients with pre-existing DM2 were stratified as poorly controlled diabetes (blood glucose [BG]>180mg/dl, median BG=216 mg/dL and median HbA1C = 8.1%), and 282 patients as having well-controlled diabetes (BG 70-180mg/dl, median BG=116mg/dL and median HbA1C=7.3%). Although both groups had similar baseline age, body mass index and chest computed tomography scan at admission, a lower incidence of lymphopenia, lower rates of increased leukocyte and neutrophil counts and an increase in serum CRP and procalcitonin were observed in the group with Controlled BG.There was also a significantly lower frequency of pharmacological therapy in the well-controlled BG group compared to the poorly controlled group.…”
Section: Glycemic Control and Covid-19 Outcomesmentioning
confidence: 99%